Effect of lanthanide on the microstructure and structure of LnMn0.5Fe0.5O3 nanoparticles with Ln=La, Pr, Nd, Sm and Gd prepared by the polymer precursor method - Romero, Mariano (2015)
The synthesis of LnMn0.5Fe0.5O3 perovskite nanoparticles by the polymer precursor method showed a strong intrinsic dependence with different lanthanides (Ln=La, Pr, Nd, Sm and Gd). The polymerization level reached in the polymer precursor was proportional to the atomic number of lanthanide with exception of samarium, which showed the formation of a different precursor based in a citrate chelate with ethyleneglycol bonded as adduct. The increasing level of polymerization of the polymer precursors showed the formation of large-size perovskite nanoparticles after its calcination. SAXS and TEM analyses suggested that nanoparticles obtained, using this method, have a squared-like microstructure in connection with the polymer precursor microstructure. Structural analysis showed an orthorhombic structure with a slight decline in the Jahn-Teller distortion when the atomic number of lanthanide increases. Mössbauer spectroscopy showed the presence of a majority site in agreement with the Pbnm orthorhombic structure best fitted with Rietveld refinements and in some cases, a more distorted site attributed to local inhomogeneities and oxygen vacancies.